2017
DOI: 10.14233/ajchem.2017.20899
|View full text |Cite
|
Sign up to set email alerts
|

A Bioanalytical Method Development and Validation for Simultaneous Determination of Velpatasvir and Sofosbuvir in Spiked Human Plasma

Abstract: INTRODUCTION Sofosbuvir ( Fig. 1) is a prodrug of 2'-deoxy-2'-fluoro-2'-C-methyl-uridine monophosphate that is phosphorylated intra cellularly to the active triphosphate form, used for the treatment of chronic hepatitis C. The nucleoside triphosphate is a nonobligate chain-terminating analogue of UTP that competes for incorporation at the HCV NS5B polymerase active site. Viral RNA synthesis is inhibited secondary to incorporation of the phosphorylated metabolite into nascent viral RNA by the HCV RNA-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The literature survey revealed that there are few stability indicating RP-HPLC 5,6,7,8,9,10 and UV 11 spectrophotometric methods are available for the simultaneous estimation of Sofosbuvir and Velpatasvir in tablet dosage form. Few analytical methods for Sofosbuvir and other HCV drugs in biological fluids by UPLC-MS/MS have been reported 12,13,14,15,16 . However, a stability indicating UPLC method was not available.…”
Section: Quick Response Codementioning
confidence: 99%
“…The literature survey revealed that there are few stability indicating RP-HPLC 5,6,7,8,9,10 and UV 11 spectrophotometric methods are available for the simultaneous estimation of Sofosbuvir and Velpatasvir in tablet dosage form. Few analytical methods for Sofosbuvir and other HCV drugs in biological fluids by UPLC-MS/MS have been reported 12,13,14,15,16 . However, a stability indicating UPLC method was not available.…”
Section: Quick Response Codementioning
confidence: 99%